THE EFFECT OF MANAGERIAL OWNERSHIP, BONUS COMPENSATION, FIRM SIZE, AND PROFITABILITY ON EARNING MANAGEMENT - Mohamad Waliyya Amananto; Titiek Suwarti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study intends to determine the effect of Managerial Ownership, Bonus Compensation, Firm Size, and Profitability on Earning Management for manufacturing sector companies that are listed on the Indonesia Stock Exchange in 2020-2022. The population in this study is manufacturing sector companies listed on Indonesia Stock Exchange in 2020-2022. The technique of sampling in this study is purposive sampling. The total number of companies as samples is 45 and the total number of data samples for 3-year observation is 135. The analysis technique used in this study is multiple linear analysis with an SPSS application. The result of this study is Managerial Ownership, Bonus Compensation, Firm Size, and Profitability simultaneously affect Earning Management. Partially, Managerial Ownership affects Earning Management in the negative direction, Bonus Compensation affects Earning Management in the negative direction, Firm Size does not affect Earning Management, and Profitability does not affect Earning Management. Keywords: Managerial Ownership, Bonus Compensation, Firm Size, Profitability, and Earning Management